Maternal Complications of Severe Preeclampsia at Tugurejo Hospital, Semarang, 2016-2020 - Widyadhana, Indra Renata; Sudiat, Muhamad; Fuad, Wijayanti (Berkala Kedokteran, 2024)
Preeclampsia is a condition accompanied by hypertension and proteinuria in pregnancy. Preeclampsia is divided into mild preeclampsia, severe preeclampsia, and superimposed preeclampsia on chronic hypertension. Severe preeclampsia is characterized by systolic pressure ≥160 mmHg and/or diastolic ≥110 mmHg, thrombocytopenia (<100,000 µL), and serum creatinine level >1.1 mg/dl or creatinine level increased from normal levels without coexisting kidney disease. Severe preeclampsia can cause several complications for the mother and fetus. Descriptive research with cross sectional design and retrospective approach. Sampling was in the form of medical records; this study used a total sampling method with a population from 1 January 2016 to 31 December 2020. This research was conducted in February 2022 - March 2022 at Tugurejo Hospital, Semarang. Obtained the results of normal delivery as much as 89.5% and severe preeclampsia as much as 588 10.5%, ideal maternal age as much as 73% and risky maternal age as many as 159 cases 27%. In severe preeclampsia with the ideal age, vaginal delivery 51.0%, multigravidas 64.1%, term delivery age 62.5%, no history of hypertension or severe preeclampsia in previous pregnancies 86.7%, and the most complications was pulmonary edema (2.3%). In severe preeclampsia at risk age, vaginal delivery was 52.8%, multigravida was 86.8%, term delivery was 63.5%, had no history of hypertension or severe preeclampsia in previous pregnancies was 64.2%, and complications the most was pulmonary edema (5.7%). The ratio of normal births to severe preeclampsia is 8:1, severe preeclampsia occurs mostly in women of ideal age,At the ideal age and at risk, the majority are abdominal, multigravida, term deliveries, have no history of hypertension and preeclampsia, and the complications found includepulmonary edema, eclampsia, postpartum hemorrhage, placental abruption, HELLP syndrome, heart failure, thrombocytopenia, acute renal failure, hepatic rupture, and maternal death.